Short-Term Angiotensin II Treatment Affects Large Artery Biomechanics and Function in the Absence of Small Artery Alterations in Mice - Leloup, Arthur J. A.; De Moudt, Sofie; Van Hove, Cor E.; Dugaucquier, Lindsey; Vermeulen, Zarha; Segers, Vincent F. M.; De Keulenaer, Gilles W.; Fransen, Paul (Frontiers in Physiology, 2018)
Induction of hypertension by angiotensin II (AngII) is a widely used experimental stimulus to study vascular aging in mice. It is associated with large artery stiffness, a hallmark of arterial aging and a root cause of increased cardiovascular risk. We reported earlier that long term (4 week) AngII treatment in mice altered the active, contractile properties of the arteries in a vascular bed-specific manner and that, in healthy mice aorta, active contractile properties of the aortic wall determine isobaric aortic stiffness. Given the huge physiological relevance of large artery stiffening, we aimed to characterize the early (1 week) changes in the active properties of the aorta of AngII-treated mice. We were not able to detect a significant effect of AngII treatment on anesthetized blood pressure or abdominal aorta pulse wave velocity. Ex vivo biomechanical and functional studies of the aorta revealed increased arterial stiffness and altered vascular smooth muscle cell (VSMC) and endothelial cell reactivity. Interestingly, the AngII-associated changes in the aorta could be largely attributed to alterations in basal VSMC tone and basal nitric oxide efficacy, indicating that, besides structural remodeling of the arterial wall, dysfunctional active components of the aorta play a crucial role in the pathophysiological mechanisms by which AngII treatment induces arterial stiffness.